Customer Relationship Management: A Tool for Customer Loyalty (A Case Study of Some Selected Hotels in Hawassa) - Walelign, Andualem (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
The main aim of this study was to investigate customer relationship management and customers’ loyalty in Hawassa city selected hotels by applying CRM dimensions of bonding, communication, conflict handling, empathy, responsiveness and trust. Convenience sampling technique was used to collect data from customers of the selected hotels. In line with the objective, descriptive research methods were used to examine the customers’ perceptions of CRM practices and future behavioral intentions. Inferential statistics were used to see the relationship between dependent and independent variables as well as to investigate cause and effect relationships. The key finding showed that there was a positive and significant effect of CRM dimensions of communication, conflict handling, empathy and trust on customer loyalty and selected hotel guests loyalty status shows that they were slightly intended to be loyal customer to the selected hotels. Bonding and responsiveness did not significantly affect guests’ loyalty.